WELL-BEING, PHYSICAL ACTIVITY, AND RESPONSE TO PHYSICAL ACTIVITY IN PATIENTS WITH STAGE II HYPERTENSION AND FREQUENT EXTRASYSTOLES - Ivankova, A.V.; Kuzminova, N.V.; Lozinsky, S.E.; Knyazkova, I.I.; Ivanov, V.P.; Poberezhets, O.L.; Romanova, V.O. (World of Medicine and Biology, 2025)
A total of 124 patients with stage II hypertension and frequent symptomatic extrasystoles aged 27 to 75 years were examined. They formed the main clinical sample of the study. Supraventricular extrasystoles (SVE) were recorded in 74 (59.7 %) patients, and ventricular (VE) in 50 (40.3 %) patients. It should be assumed that in patients with stage II hypertension and frequent extrasystole, the supraventricular variant is more common. Also, we examined 32 patients with stage II hypertension without any cardiac arrhythmias who were included in the comparison group. In addition to the mandatory examination methods, all patients were analyzed using visual analog scales of well-being and physical activity and an exercise test. Patients with frequent extrasystole, regardless of the location, have significantly (p
Keywords: stage II arterial hypertension; supraventricular extrasystole; ventricular extrasystole; Holter ECG monitoring; exercise test